``Presidential System of the USA through a Prism of the Roman Republic`` - Apostolovska Stepanoska, Milena; Runcheva-Tasev, Hristina (Macedonian Political Science Forum, 2016)
The United States is an original and best-known model of a presidential system in the world. Its originality is incontestable, but its roots may be found in the history of the Roman Republic as a universal and timeless model of the organization of government. The authors argue that there is a strong impact on the legacy of the Roman Republic on the modern concept of the presidential system in the United States by drawing many similarities and parallels between them. Therefore, this paper analyses wheather Polybius and his works influenced the ``founding fathers`` of modern America.